الدين والدولة بين باروخ سبينوزا ومالك بن نبي - بن الذيب جموعي; لعموري شهيدة (University of Eloued جامعة الوادي, 2024)
Abstract: This study tends to present an epistemological approach on the relationship between religion and the state between two legends of Western and Arab human thought, starting with the Dutch philosopher Baruch Spinoza, and finally with the Algerian thinker Malek Bennabi. Where this study assumes that religion as a divine authority is the basis for the success of the state as a social authority, and this His example is in the first Hebrew state and the Islamic state at the time of prophecy and the rightly guided caliphate. The study also considers that Spinoza and Malik bin Nabi concluded that the decline and impotence of states is due to the deviation of religious practices in state policy. Therefore, our study concludes with two solutions to the problem of the relationship between the religious and the political according to Each of the philosophers, the Spinozian solution sees secularism as the way to limit political rule in the name of religion, and this is due to the nature of the Western environment and the Jewish religion that is subject to distortion, while Malik bin Nabi focuses on the role of religious reference as moral values and a source of political spirit, and this is due to the nature of the Arab and Islamic environment. ملخص: تتجه هذه الدراسة إلى تقديم مقاربة معرفية حول العلاقة بين الدين والدولة بين اثنين من أساطير الفكر الإنساني الغربي و العربي، بداية بالفيلسوف الهولندي باروخ سبينوزا ،وختاما بالمفكر الجزائري مالك بن نبي .حيث تفترض هذه الدراسة أن الدين كسلطة إلهية هو أساس نجاح الدولة كسلطة اجتماعية، وهذا مثاله في الدولة العبرانية الأولى والدولة الإسلامية زمن النبوة والخلافة الراشدة ،كما تعتبر الدراسة أن سبينوزا و مالك بن نبي خلصا إلى أن انحطاط الدول و عجزها يرجع إلى انحراف الممارسات الدينية في سياسة الدولة ، بالتالي تخلص دراستنا إلى حلين لمشكلة العلاقة بين الديني و السياسي حسب كل من الفيلسوفين، فالحل السبينوزي يرى في العلمانية هي المنفذ للحد من الحكم السياسي باسم الدين وهذا لطبيعة البيئة الغربية و الدين اليهودي المتعرض للتحريف، أما مالك بن نبي فيركز على دور المرجعية الدينية كمبادئ قيمية أخلاقية ومنبعا للروح السياسية وهذا لطبيعة البيئة العربية والإسلامية.
دراسة مقاربة
Keywords: دين; دولة; سياسة; سبينوزا; مالك بن نبي; Religion; state; politics; Spinoza; Malik Bennabi